Peluang Wirausaha Mandiri melalui Pengembangan Produk Makanan dari Pangan Lokal Gorontalo - Frida Maryati Yusuf; Supartin Supartin; Nurul Fajriani Usman (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2023)
he goal of point 2 of the Sustainable Development Goals (SDGs), namely no hunger in the village, achieving food sovereignty, improving nutrition, and promoting sustainable agriculture is one of the expected forms of achievement in the implementation of the Thematic Village Development KKN program through a community service program that aims to encouraging the realization of a village without hunger, increasing community knowledge and being able to innovate based on the results of lecturers' dedication in order to improve the standard of living of the community in accordance with the achievement of the SDGs. Based on these goals, in order to reduce poverty and hunger in villages, it is necessary to strengthen food security. Empowerment and assistance programs for the community in high selling value with hydroponic cultivation technology in residents' yards really support the achievement of SDGs point 2